First parasitological study of the African clawed frog (Xenopus laevis, Amphibia) in Chile - Castillo, Cristóbal (2017)
Introduced species can arrive into new territories with parasites; however, these species are expected to face lower parasite richness than in their original regions. Both introduced hosts and parasites can affect native fauna. Since their release into the wild in Chile following laboratory use, Xenopus laevis Daudin, 1802 has widely spread throughout central Chile. The only pathogen described on the host is the fungus Batrachochytrium dendrobatidis Longcore, Pessier, Nichols, 1999; thus, this is the first parasitological study of this species in Chile. In 10 localities in central Chile, 179 specimens of X. laevis were captured and examined for parasites in the gastrointestinal tube, cavities, lungs, liver, and skin. Only nine specimens of the genus Contracaecum Railliet, Henry, 1912 were found in six specimens of X. laevis from a private dam in La Patagua. It is likely that these parasites originated from species of native birds. This is the first record of Contracaecum sp. in Chilean amphibians.